2021
DOI: 10.1111/jocn.15663
|View full text |Cite
|
Sign up to set email alerts
|

The quandary of registered nurses untrained in adult intellectual disability nursing when caring for this diverse patient group in acute care settings: An integrated literature review

Abstract: Aims and Objectives To critically appraise relevant literature on the lived experiences of registered nurses caring for adults with intellectual disability in the acute care setting in Australia to determine current knowledge and gaps in the literature. Background People with intellectual disability have the right to the highest attainable health care the same as everyone else. However, inequities still exist in the delivery of health care across the globe, including Australia that result in poorer health outc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
11
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 17 publications
(11 citation statements)
references
References 36 publications
0
11
0
Order By: Relevance
“…56,65 HCPs untrained in caring for people with ID report barriers, including low levels of competence and confidence in caring for individuals with ID. 66,67 The shared recognition of educational and training needs between PC and ID services, with the common goal of optimizing EOL care for individuals with ID, provides ample opportunity to partner for improvement. Much can be learned and optimized from all sides of this essential work, and all efforts should prioritize the person with ID.…”
Section: Tip #9: Patients With Id Benefit Tremendously From Including...mentioning
confidence: 99%
“…56,65 HCPs untrained in caring for people with ID report barriers, including low levels of competence and confidence in caring for individuals with ID. 66,67 The shared recognition of educational and training needs between PC and ID services, with the common goal of optimizing EOL care for individuals with ID, provides ample opportunity to partner for improvement. Much can be learned and optimized from all sides of this essential work, and all efforts should prioritize the person with ID.…”
Section: Tip #9: Patients With Id Benefit Tremendously From Including...mentioning
confidence: 99%
“…The title of the Regional Hospital Passport also requires further review as reference to 'hospital' was identified as limiting the wider utilisation beyond hospitals including General Practitioner and dental practices and community health services. Howie et al (2021) suggests that the lack of confidence in supporting people with intellectual disabilities is largely associated with inadequate education. Therefore, Registered Nurses in the acute hospitals often feel underprepared to provide effective care and support.…”
Section: Discussionmentioning
confidence: 99%
“…9,21,[28][29][30] Similarly, knowledge gaps exist for HAPC clinicians caring for individuals with ID related to communication, decision-making, and complex ID-related medical conditions. 12,31 A lack of formal protocols, policies, and guidelines regarding EOL care for people with ID contributes to the gaps in knowledge and care for DSPs and HAPC clinicians. 25…”
Section: The Role Of the Dsp For People With Idmentioning
confidence: 99%
“…Direct support professionals report varying knowledge and experiences related to death and dying, 21,26 a lack of experience or training in the provision of EOL care, 27 and feel ill-equipped to support individuals with ID with the aspects of EOL 9,21,28-30 . Similarly, knowledge gaps exist for HAPC clinicians caring for individuals with ID related to communication, decision-making, and complex ID-related medical conditions 12,31 . A lack of formal protocols, policies, and guidelines regarding EOL care for people with ID contributes to the gaps in knowledge and care for DSPs and HAPC clinicians 25 …”
Section: Caregiver Considerations For People With Idmentioning
confidence: 99%